Getting the agenda right for higher education in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, at the start of a new academic year in Macau’s higher education (HE). What will students learn? What kind of people are the institutions turning out? For example, look at the thousands of students studying business and technology in Macau, the big recruiters in HE.